1996
DOI: 10.1063/1.116601
|View full text |Cite
|
Sign up to set email alerts
|

Structure and magnetic properties of epitaxial spinel ferrite thin films

Abstract: We have grown epitaxial spinel ferrite thin films of (Mn,Zn) Fe2O4 and CoFe2O4 on (100) and (110) SrTiO3 and MgAl2O4 buffered by spinel structure buffer layers. High quality spinel ferrite films were grown at 400 °C on buffer layers that were grown at 600 °C and postannealed at 1000 °C. Although (Mn,Zn) Fe2O4 grown directly on SrTiO3 and MgAl2O4 shows mediocre structural and magnetic properties, ferrite films grown on (100) and (110) SrTiO3 and MgAl2O4 buffered with CoCr2O4 exhibit excellent crystallinity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
81
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(88 citation statements)
references
References 0 publications
3
81
0
1
Order By: Relevance
“…The magnetism in ferrite thin films has been shown to be very sensitive to effects such as strain 20 and stoichiometry, 13 while the structure and chemistry at the interfaces in spinfilter-based tunnel junctions are also known to play a crucial role in the spin-filtering efficiency. Our structural study therefore began with in situ RHEED analyses performed in real time throughout the deposition process.…”
Section: A Structural and Chemical Characterizationsmentioning
confidence: 99%
“…The magnetism in ferrite thin films has been shown to be very sensitive to effects such as strain 20 and stoichiometry, 13 while the structure and chemistry at the interfaces in spinfilter-based tunnel junctions are also known to play a crucial role in the spin-filtering efficiency. Our structural study therefore began with in situ RHEED analyses performed in real time throughout the deposition process.…”
Section: A Structural and Chemical Characterizationsmentioning
confidence: 99%
“…10,11 In contrast, on (110) surface of the substrates, the two orthogonal in-plane directions, [110] and [001], are crystallographically un-equivalent. Epitaxial thin films prepared on (110)-orientated STO, LAO, and MAO substrates would be expected to show stronger anisotropy in the film plane, 12,13 and may demonstrate some metastable structure and fascinating properties which were not observed in its bulk. It was reported that the BiFeO 3 thin film grown on the (110)-oriented LAO substrate exhibits a monoclinic structure and a unique stripe ferroelectric domain configuration with a large theoretical polarization of 130 µc/cm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] This interest is motivated by potential applications such as magnetic thin-film read heads, 4 cladding layers for thin film inductors, 5 and microwave acoustic devices. 2 For most applications, two of the most important parameters are the resistivity of the layer and the ac permeability, . While the resistivity is similar to that of the bulk the permeability of the thin ferrite films, on which many authors do not report explicitly, appears to be significantly less.…”
Section: Introductionmentioning
confidence: 99%